2014
DOI: 10.15197/sabad.1.11.06
|View full text |Cite
|
Sign up to set email alerts
|

Rhinomanometric Assessment of The Impact of High Altitude on Nasal Airway Resistance

Abstract: Aim of this study is to carry out a rhinomanometric assessment for the impact of altitude variation (1050-2215m)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Evaluation of total airway resistance (pre-decongestion) on induction and after 2 months was found to be within the normal range without any significant change during the stay at high altitude. According to Karatas et al 10 the total nasal airway resistance in climbers to high altitude in short stay of less than a week were within the normal physiological limits and this is in agreement with the present study. Further on in the present study the same subjects evaluated after 2 months of stay at high altitude had shown no change in total nasal airway resistance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Evaluation of total airway resistance (pre-decongestion) on induction and after 2 months was found to be within the normal range without any significant change during the stay at high altitude. According to Karatas et al 10 the total nasal airway resistance in climbers to high altitude in short stay of less than a week were within the normal physiological limits and this is in agreement with the present study. Further on in the present study the same subjects evaluated after 2 months of stay at high altitude had shown no change in total nasal airway resistance.…”
Section: Discussionsupporting
confidence: 94%
“…There are multiple factors that affect the nasal mucosa such as cold air which is seen to increase nasal airway resistance 12 and hypercapnia induced by rarified atmosphere at high altitude causing vasoconstriction of nasal mucosa, interplay to keep the total airway resistance unaltered. 10 Other factors like antihistaminics, nasal steroids and smoking habits are also known to affect nasal airway resistance and so the subjects were asked to avoid them in the present study.…”
Section: Discussionmentioning
confidence: 99%